The importance of developing interprofessional practice in the training of nutrition professionals: a narrative review (Research, Society and Development, 2022)
Working as a team is one of the key points to ensure effectiveness in comprehensive care for any individual. Thus, interprofessional education is consolidated when two or more professions work together, producing knowledge that corroborates the resolute care of users in health services. This article is a narrative review, which aimed to analyze studies on the role of the Nutrition professional inserted in interprofessional teams and reflect on the importance of interprofessional education for health professionals. The articles compiled in this study were selected through the following databases: PubMed, Lilacs and Scielo. The survey was limited to articles published in English and Portuguese, without a time frame, using the standardized descriptors: Interprofessional Relations; Nutritionists; Health Professional and its correspondents in English, the Boolean operator And was used in all combinations. It was observed that within the vast dimensions of the health area, no single professional will be able to carry out all the actions that comprise the health care of individuals, so it is imperative to unite different professions and knowledge. Thus, the literary findings indicate that the science of nutrition has been recognized as an important area in promoting health and guaranteeing quality of life, and its insertion in interprofessional care teams is essential.